silver (foxes) (1970)
silver n . . . furring and trapping occupy much of the Eskimoes' attention during the winter. The white, red, blue, and so-called "silver" foxes are hunted for their skins, which command a good price in the European Market. PRINTED ITEM DNE-cit G.M.Story AUG 1970 JH AUG 1970 Used I and Sup Used I and Sup 2 Used I ~ fir/fox/hair (fox)/jar/thaw/ patch fox, GLITTER, PATCH FOX.